PENGGUNAAN WEBSITE PORTAL BERITA SEBAGAI MEDIA INFORMASI UNTUK MAHASISWA - Faizal, Mochammad; Abdillah, Muhammad Faqih; Sari I.M.S, Dea Aulia; Setiadi, Wahyu; Octavia, Denisha; Suhendari, Wulan; Soewardikoen, Didit Widiatmoko (Institut Bisnis dan Teknologi Indonesia, 2018)
Abstract Website can serve as a medium to deliver information, related to academic and non-academic university activity. Telkom University as a technology-based university is appropriate to use the website as a means of supporting the activity going on inside. On the one hand, 55 Student Activity Units at Telkom University require publication media related to non-academic activities conducted. Related to this, there are already three official media that can accommodate it, but the results of the questionnaire said that students still feel that the dissemination of information is still not optimal. This is important, because website is the main channel used to disseminate information in real time. To answer these problems, the necessary data will be obtained through visual objects observation, interviews with experts, distributing questionnaires to the audience, as well as literature studies that related to relevant theories. Once the data is collected, it will be analyzed through comparative matrix to obtain conclusions and suggestions that can answer the formulation of research problems. This research aims to optimize the cyber media websites to deliver real-time and reliable information to students. The results obtained are standard forms that can be used to create an actual and trusted student news portal website.